Associations between the perceived quality of the coach–athlete relationship and athlete burnout: An examination of the mediating role of achievement goals. (January 2016) - Isoard-Gautheur, Sandrine; Trouilloud, David; Gustafsson, Henrik; Guillet-Descas, Emma
Abstract: Objectives: The aim of the current study was to examine (1) associations between the quality of the coach–athlete relationship as perceived by athletes and athlete burnout and, (2) the role of achievement goals in mediating the association between the coach–athlete relationship and burnout. Design: Cross-sectional. Method: 359 athletes completed measures of the perceived quality of the coach–athlete relationship (the 3Cs model), achievement goals (the 2 × 2 model) and burnout (the athlete burnout model). Results: Structural equation modeling revealed negative relationships between the perceived quality of the coach–athlete relationship and the three dimensions of athlete burnout (df = 118, χ² = 215.37, RMSEA = .05 [.04; .06], TLI = .97, CFI = .97). Moreover, results suggested that mastery-approach goals partially mediated the relationship between the coach–athlete relationship and two dimensions of athlete burnout: sport devaluation (i.e., indirect and direct effects: p  < .001) and reduced accomplishment (i.e., indirect and direct effects: p  < .01). Conclusion: The current study confirms and broadens previous knowledge on the socio-cognitive correlates of athlete burnout by demonstrating that the level of athlete burnout is associated with the perceived quality of the relationship with the coach. Results also highlight that achievement goals partially mediate these relationships. Highlights: The coach–athlete relationship is positively linked to mastery-approach goals. Mastery-approach goals are negatively linked to burnout. Mastery-avoidance goals are positively linked to burnout. The coach–athlete relationship is negatively linked to burnout. This last relationship is partially mediated by mastery-approach goals.